2007
DOI: 10.1080/00102200701407887
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Flame Liftoff Height of Diffusion/Partially Premixed Jet Flames and Modeling of Mild Combustion Burners

Abstract: In this article, a new flame extinction model based on the k=e turbulence time scale concept is proposed to predict the flame liftoff heights over a wide range of coflow temperature and O 2 mass fraction of the coflow. The flame is assumed to be quenched, when the fluid time scale is less than the chemical time scale (Da < 1). The chemical time scale is derived as a function of temperature, oxidizer mass fraction, fuel dilution, velocity of the jet and fuel type. The present extinction model has been tested fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 46 publications
1
41
0
Order By: Relevance
“…Because the jet exit diameter was the same for each experimental case, it follows that in order for ε to be constant for a given fuel (ρ 0 ) 1/2 /u must also be constant. To calculate u for the flames with co-flow analyzed in Moore et al [11] (where the methane is undiluted at the jet exit), an effective velocity is used where C = 40 [9] and all subscripts cf refer to characteristics of the co-flow. Using this velocity gives a range of ε from 3.9 to 4.9 and an average ε of 4.35, a value in good agreement with previous studies.…”
Section: Resultsmentioning
confidence: 99%
“…Because the jet exit diameter was the same for each experimental case, it follows that in order for ε to be constant for a given fuel (ρ 0 ) 1/2 /u must also be constant. To calculate u for the flames with co-flow analyzed in Moore et al [11] (where the methane is undiluted at the jet exit), an effective velocity is used where C = 40 [9] and all subscripts cf refer to characteristics of the co-flow. Using this velocity gives a range of ε from 3.9 to 4.9 and an average ε of 4.35, a value in good agreement with previous studies.…”
Section: Resultsmentioning
confidence: 99%
“…The advantages of MILD combustion are already reaching industry: Danon (2011) reported an increase in demand for expertise on the implementation of MILD combustion, especially for large-scale furnaces equipped with multiple burners. MILD combustion has been achieved experimentally (Cabra et al, 2003(Cabra et al, , 2005Derudi and Rota, 2011;Derudi et al, 2007aDerudi et al, , 2007bDerudi et al, , 2007cErtesvag and Magnussen, 2000;Hasegawa et al, 2002;Kraus and Barraclough, 2012;Kumar et al, 2007;Li and Mi, 2010;Li et al, 2010aLi et al, , 2010bMi et al, 2010;Mörtberg et al, 2007;Oldenhof et al, 2010Oldenhof et al, , 2011Özdemir and Peters, 2001;Rafidi and Blasiak, 2006;Sabia et al, 2007;Weber et al, 2000;Yuan and Naruse, 1999;Zhenjun, Tong and Chaohua, 2010) and numerically (Awosope et al, 2006;Cabra et al, 2003Cabra et al, , 2005Coelho and Peters, 2001;Ertesvag and Magnussen, 2000;Frassoldati et al, 2010;Galletti et al, 2009;Kim et al, 2005;Kraus and Barraclough, 2012;Kumar et al, 2007;Oldenhof et al, 2010;Park et al, 2003;Szegö, 2010;Zhenjun et al, 2010) in premixed, partially-premixed and non-premixed combustio...…”
Section: Combustion Efficiencymentioning
confidence: 99%
“…For the MILD flame, to determine the lift-off height a certain threshold level for an averaged quantity is defined. The use of variables such as temperature (Kumar, Paul and Mukunda, 2007), OH concentration (Cabra et al, 2003;Ertesvag and Magnussen, 2000) and luminescence (Cabra et al, 2005) were proposed.…”
Section: Open Furnacementioning
confidence: 99%
“…4, where the flame has a relative large angle θ [close to 90] from the jet direction, and the blow-out is mainly dominated by the cross flow). It was reported that the effective velocity [6][7][8], which combines the effects from the fuel jet and the co-flow, can be calculated as eff e e co co…”
Section: A Physical Model Based On the Damköhler Numbermentioning
confidence: 99%
“…Broadwell et al [5] proposed a large-scale mixing model and defined as a criterion of the ratio between the chemical reaction time and the turbulent mixing time to characterize the stability of turbulent diffusion flames. The effect of coflow air on the blow-out limit was also investigated [6][7][8][9][10][11][12][13][14][15] and an effective velocity was proposed. The effect of coflow air temperature was also studied [16,17].…”
Section: Introductionmentioning
confidence: 99%